(untitled) (Revista ABRA, 2021)
In Costa Rica, as in other countries in the region, most social spaces have consolidated around trails, roads and highways that interconnect communities and regions. As more and more roads are being built, and the number of cars in use continues to grow, cultural changes are generated that condition the dynamics of mobility within societies and among users of the road system, often leading to conflicts in the form of traffic accidents with serious individual, family and social repercussions. The perspective of Social Sciences allows a wider reading and deeper knowledge of the needs that affect exposure to the risk of an automobile crash and the characteristics that determine mobility patterns in the large cities of Costa Rica’s Central Valley, in its emerging cities, and in rural areas. Participation of social scientists in theoretical debates and decision making on public policies related to mobility and road safety is essential to overcome the car-centric model that continues to prevail in the management of the road system.